ASEAN'S EFFORTS AS REGIONAL ORGANINIZATION IN COMBATING ARMS SMUGGLING IN SOUTHEAST ASIA - Umaya Khusniah (Universitas Muhammadiyah Yogyakarta, 2011)
UNITED NATION ACKNOWLEDGE MORE THAN SEVEN TRANSNATIONAL CRIMES, BUT ASEAN ACKNOWLEDGE FIVE CRIMES WHICH INCLUDE IN TRANSNATIONAL CRIME